Online Education in North Cyprus Universities: Case Study Eastern Mediterranean University - Oroja, Shola; Kotoua, Selira; İlkan, Mustafa (Procedia - Social and Behavioral Sciences, Elsevier, 2011)
Online education, known as distance learning or e-learning is different from traditional education because students are not required to visit an actual classroom and listen to an instructor face to face. Universities have used the internet as a tool for teaching .Online education program in the Eastern Mediterranean University (EMU) is still in it’s infancy and working gradually to catch up with other Universities in Turkey. Using questionnaires as the data source, this paper will examine the importance of online courses and gauge people’s opinion about online courses in universities in Northern Cyprus with the Eastern Mediterranean University as a “case study”
The file in this item is the publisher version (published version) of the article.
Keywords: Online education; Eastern Mediterranean University (EMU); E-learning